2023
DOI: 10.3389/fgene.2023.1129476
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new co-diagnostic genes for sepsis and metabolic syndrome using single-cell data analysis and machine learning algorithms

Abstract: Sepsis, a serious inflammatory response that can be fatal, has a poorly understood pathophysiology. The Metabolic syndrome (MetS), however, is associated with many cardiometabolic risk factors, many of which are highly prevalent in adults. It has been suggested that Sepsis may be associated with MetS in several studies. Therefore, this study investigated diagnostic genes and metabolic pathways associated with both diseases. In addition to microarray data for Sepsis, PBMC single cell RNA sequencing data for Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Several researched have elucidated that CFLAR is associated with immune regulation, cardiac remodeling, and acute liver injury 29 31 . In the context of sepsis, CFLAR has been identified on neutrophils 32 , and it has been shown to down-regulate lipopolysaccharide-induced NF-κB activation 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Several researched have elucidated that CFLAR is associated with immune regulation, cardiac remodeling, and acute liver injury 29 31 . In the context of sepsis, CFLAR has been identified on neutrophils 32 , and it has been shown to down-regulate lipopolysaccharide-induced NF-κB activation 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Linfeng Tao et el. Found new co-diagnostic genes for sepsis and metabolic syndrome through single-cell data analysis and machine learning algorithms [ 33 ]. Recently, Wenfeng Xie also found SPI1-mediated autophagy of peripheral blood monocytes during sepsis based on single-cell RNA sequencing [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the diagnostic value of STAT3 in sepsis-induced myocardial disease and sepsis-related respiratory distress syndrome ( Zhang et al, 2019 ; Song et al, 2023 ). Metabolism-related genes ( She et al, 2022 ), necrosis-related genes ( She et al, 2023 ), immune-related genes ( Zheng et al, 2022 ) common DEGs related to sepsis and metabolic syndrome ( Tao et al, 2023 ), apoptosis-related genes ( Wang et al, 2022 ), inflammation response signature genes ( Jiang et al, 2022 ), and signature genes for septic shock in children ( Fan et al, 2022 ) have all shown some efficacy in the diagnosis and prognostic assessment of sepsis. In addition, metabolites based on metabolomics analysis ( Li Y. et al, 2023 ), m6A regulatory factors ( Li F. et al, 2023 ), and non-coding RNAs such as miR-147b ( Trung et al, 2021 ), lncRNA THAP9-AS1 , and TSPOAP1-AS1 ( Wu et al, 2020 ) have all been reported as potential diagnostic or prognostic indicators for sepsis or septic shock.…”
Section: Discussionmentioning
confidence: 99%